2020
DOI: 10.3390/cancers12113431
|View full text |Cite
|
Sign up to set email alerts
|

CPT1A Over-Expression Increases Reactive Oxygen Species in the Mitochondria and Promotes Antioxidant Defenses in Prostate Cancer

Abstract: Cancers reprogram their metabolism to adapt to environmental changes. In this study, we examined the consequences of altered expression of the mitochondrial enzyme carnitine palmitoyl transferase I (CPT1A) in prostate cancer (PCa) cell models. Using transcriptomic and metabolomic analyses, we compared LNCaP-C4-2 cell lines with depleted (knockdown (KD)) or increased (overexpression (OE)) CPT1A expression. Mitochondrial reactive oxygen species (ROS) were also measured. Transcriptomic analysis identified ER stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 63 publications
1
25
1
Order By: Relevance
“…Cpt1a fuels lipid β-oxidation by producing acyl-carnitines in the mitochondria ( 39 ). It was recently demonstrated that in prostate cancer cell models, overexpression of Cpt1a is associated with a significant increase in intracellular lipase activity ( 40 ), a step that liberates fatty acids from triglyceride stores, which can then be used for β-oxidation ( 41 ). Consequently, overexpression of Cpt1a increases free fatty acid (FFA) content in these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cpt1a fuels lipid β-oxidation by producing acyl-carnitines in the mitochondria ( 39 ). It was recently demonstrated that in prostate cancer cell models, overexpression of Cpt1a is associated with a significant increase in intracellular lipase activity ( 40 ), a step that liberates fatty acids from triglyceride stores, which can then be used for β-oxidation ( 41 ). Consequently, overexpression of Cpt1a increases free fatty acid (FFA) content in these cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated that androgen withdrawal (which mimics the standard of care therapy for metastatic PCa) increases CPT-1A expression and FAO activity, which supports CRPC growth and antiandrogen resistance by supplying acetyl groups for histone acetylation ( 117 ). In a follow-up study, the authors showed that CPT-1A overexpression promotes antioxidant defenses, which foster PCa progression ( 118 ). Finally, last year, the group put forward the involvement of FAO in immunomodulation.…”
Section: Lipid Metabolism Rewiring In Pca Development and Progressionmentioning
confidence: 99%
“…Finally, last year, the group put forward the involvement of FAO in immunomodulation. Using the TRAMPC1 PCa model, the authors demonstrated that FAO inhibition with ranolazine decreases Tim3 content in CD8+ tumor-infiltrating T cells, increases macrophages, and decreases blood myeloid immunosuppressive monocytes, suggesting that targeting FAO stimulates anti-cancer immunity ( 118 ).…”
Section: Lipid Metabolism Rewiring In Pca Development and Progressionmentioning
confidence: 99%
“…Urological Cancer 2020 contains three reviews [ 31 , 32 , 33 ] and seven articles [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ] about prostate cancer. Sarkar et al [ 31 ] reviewed the intimate mechanisms of angiogenesis in prostate cancer and their possible blockade to maximize benefits minimizing toxicity.…”
mentioning
confidence: 99%
“…The authors considered this effect as a potential target to develop new therapeutic strategies in castration-resistant prostate cancers. Transcriptomic and metabolomic analyses of LNCaP-C4-2 cell lines with depleted and increased CPT1A (carnitine palmitoyl transferase 1) expression, respectively, were investigated [ 40 ]. CPT1A plays an important role in the adaptation to stress and antioxidant production and is an enzyme involved in lipid catabolism and may be critically involved in promoting neuroendocrine differentiation in prostate cancer cells.…”
mentioning
confidence: 99%